Expanding protected area coverage for migratory birds could improve long-term population trends - Border, Jennifer A; Pearce-Higgins, James W; Hewson, Chris M; Howard, Christine; Stephens, Philip A; Willis, Stephen G; Fuller, Richard A; Hanson, Jeffrey O; Sierdsema, Henk; Foppen, Ruud P B; Brotons, Lluís; Gargallo, Gabriel; et al. (Nature communications, 2025)
Populations of many migratory taxa have been declining over recent decades. Although protected areas are a cornerstone for conservation, their role in protecting migratory species can be incomplete due to the dynamic distributions of these species. Here, we use a pan-European citizen science bird occurrence dataset (EurobirdPortal) with Spatiotemporal Exploratory Modelling to assess how the weekly distributions of 30 passerine and near passerine species overlap with protected areas in Europe and compare this to range adjusted policy protection targets. Thirteen of our 30 species were inadequately covered by protected areas for some, or all, of the European part of their annual cycle under a target based on the 2020 Convention on Biodiversity framework and none were adequately covered under a target based on the 2030 Convention on Biodiversity framework. Species associated with farmland had the lowest percentage of their weekly distribution protected. The percentage of a species' distribution within protected areas was positively correlated with its long-term population trend, even after accounting for confounding factors, suggesting a positive influence of protected areas on long-term trends. This emphasises the positive contribution that an informed expansion of the European protected area system could play for the future conservation of migratory land birds.
Keywords: Biodiversity; migrace zvířat; Evropa; zachování přírodních zdrojů; Conservation of Natural Resources; zvířata; Population Dynamics; Birds; ptáci; populační dynamika; biodiverzita; Europe; Animal Migration; Animals